PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PESERTA DIDIK KELAS XI-I SMA NEGERI 4 PALU - Mirnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the poetry writing skills of grade XI I students at SMA Negeri 4 Palu through the implementation of the *Culturally Responsive Teaching* (CRT) approach. The research employed a Classroom Action Research (CAR) method conducted in two cycles with 36 students as the subjects. The findings indicate that in cycle I, students’ poetry writing skills were still low, with an average score of 67.64 (poor category). After improvements in cycle II through the use of cultural video media from Central Sulawesi and intensive guidance, the average score increased to 81.67 (good category). All students achieved at least the sufficient category, with 18 students in the sufficient category, 12 in the good category, and 6 in the very good category. These results demonstrate that the CRT approach is effective in enhancing students’ poetry writing skills by connecting learning to their cultural experiences, increasing motivation, and encouraging active participation in the learning process.